(3GdbGfhfs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s ((3HeOjfI GdSdGe (B( (3HZOGO(B) s)
(3ChdgG (B:s
(3hHYO (B: (3abO GdJeS efi HYV NdU ENhGfi hef jdRefi ESYGag , HeG jSeM Hg s
(3BNQgG (B:s
(3CYVGA GdeZV GdZGdjI fGaYI ef ChLGY GdQMe GdHGQRg MehdkG hjTJQc GdQMe GdeNJfbI hGdeGjdI Je cJGH GdCOhjI GdeaQOI hgh GdcJGH GdKGfi ef cJGH GdbGfhf s
(3GdfSNI HgG MhGTs
(3ef fSNI NRGFfjI ObjbIs
(3cJH Yf CUd GHf SjfG faSg dNRGfI CHj YHO Gddg eMeO Hf YHO Gddg GdeYQi Sfg (B556s
(3hYdjgG HYV MhGTi dCejf GdOhdI CHj GdMSf gHI Gddg Hf UGYO s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdWHs